2015
DOI: 10.3390/nu7085283
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Alleviates Changes in a Rat Model of Metabolic Syndrome Induced by High-Carbohydrate, High-Fat Diet

Abstract: Metabolic syndrome is a cluster of metabolic abnormalities characterized by obesity, insulin resistance, hypertension and dyslipidemia. Ferulic acid (FA) is the major phenolic compound found in rice oil and various fruits and vegetables. In this study, we examined the beneficial effects of FA in minimizing insulin resistance, vascular dysfunction and remodeling in a rat model of high-carbohydrate, high-fat diet-induced metabolic changes, which is regarded as an analogue of metabolic syndrome (MS) in man. Male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
57
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 39 publications
10
57
1
1
Order By: Relevance
“…FA at a dose of 2.6 mmol/kg diet was effective at reducing inflammatory, hyperlipidemia, hyperglycemia markers in a highfructose, high-fat diet-induced model of metabolic syndrome [33]. A similar study found that FA minimized insulin resistance, vascular dysfunction and remodeling in a rat model of high-carbohydrate, highfat diet-induced metabolic changes, which may be realized through suppression of oxidative stress, down-regulation of p47phox, increased nitric oxide bioavailability with up-regulation of endothelial nitric oxide synthase and suppression of tumor necrosis factor-α (TNF-α) [34]. It is clear from these studies that FA simultaneously targets several aspects of metabolic syndrome including hyperglycemic indices, hypercholesterolemia markers, inflammation, oxidation and others through impacting the fundamental signaling mechanisms underlying energy metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…FA at a dose of 2.6 mmol/kg diet was effective at reducing inflammatory, hyperlipidemia, hyperglycemia markers in a highfructose, high-fat diet-induced model of metabolic syndrome [33]. A similar study found that FA minimized insulin resistance, vascular dysfunction and remodeling in a rat model of high-carbohydrate, highfat diet-induced metabolic changes, which may be realized through suppression of oxidative stress, down-regulation of p47phox, increased nitric oxide bioavailability with up-regulation of endothelial nitric oxide synthase and suppression of tumor necrosis factor-α (TNF-α) [34]. It is clear from these studies that FA simultaneously targets several aspects of metabolic syndrome including hyperglycemic indices, hypercholesterolemia markers, inflammation, oxidation and others through impacting the fundamental signaling mechanisms underlying energy metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…Phytoestrogens are known to reduce cholesterol absorption via increasing the mRNA surface expression of ABCA1 and ABCG1 transporters; resulting in cholesterol efflux (Chen & Wang, ). Additionally, Senaphan et al () reported that ferulic acid enhanced the expression of endothelial nitric oxide synthase (eNOS) and suppressed TNF‐α.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies are still relevant as it is often a hidden ingredient in herbal and over the counter slimming products (34). In this context, there are reports that FA may have health benefits by minimizing the cardiovascular complications of metabolic syndrome (35). Besides the antiobese potential of FA, this study also evaluated its likely toxicity to liver and kidney.…”
Section: Discussionmentioning
confidence: 99%